Desenvolvimento da compreensão leitora com foco na estratégia de inferência no ano final do ensino fundamental - Lussani, Brendom da Cunha (2021)
The data of the national readery proficiency, from the evaluation of PISA 2018 and SAEB 2017, indicate that the reading of Brazilian students is limited in terms of understanding the texts they read. One of the reasons students encounter difficulties in what they read is the generation of inferences. Different authors (GOODMAN, 1973; WARREN; NICHOLAS; TRABASSO, 1979; VAN DIJK, 1980; KINTSCH; VAN DIJK, 1983; MARCUSCHI, 1985; GIASSON, 2000; DELL'ISOLA, 2001; ABARCA; RICO (2003); MARCUSCHI, 2008) have already emphasized that there is a relationship between reading comprehension and the use of the inference reading strategy, and this is considered one of the main agents of the global understanding of a written text. Therefore, from the data of PISA 2018, as well as the national reading, and SAEB 2017, in the national scenario, it is proposed to analyze the reading of a group of students of the 9th grade, from a school in the interior of Rio Grande do Sul. From the analysis of the data, especially those that show the reader proficiency of the 9th grade, a reading script is organized which the generation of inference is privileged. The reading script is a prototype that can be used by Portuguese language teachers to offer subsidies for the student to generate inference and achieve the understanding of what he reads. Having been organized from questions, provides for six stages, all based on the bases of Psycholinguistics that guide this research, as well as approved by a group of specialists in Psycholinguistics and Portuguese language teachers.